2019
DOI: 10.4049/jimmunol.1801616
|View full text |Cite
|
Sign up to set email alerts
|

c-Abl–Mediated Tyrosine Phosphorylation of PARP1 Is Crucial for Expression of Proinflammatory Genes

Abstract: Poly(ADP-ribosyl)ation is a rapid and transient posttranslational protein modification mostly catalyzed by poly(ADP-ribose) polymerase-1 (PARP1). Fundamental roles of activated PARP1 in DNA damage repair and cellular response pathways are well established; however, the precise mechanisms by which PARP1 is activated independent of DNA damage, and thereby playing a role in expression of inflammatory genes, remain poorly understood. In this study, we show that, in response to LPS or TNF-a exposure, the nonrecepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 63 publications
1
27
0
Order By: Relevance
“…Evidence suggests that ADP-ribosylation participates in inflammation (Bai and Virág 2012;Rosado et al 2013;Kunze and Hottiger 2019). PARP1 has been implicated in the mechanisms for responses (e.g., proinflammatory cytokine expression) of macrophages or macrophage-like cell lines to pathogen-associated molecular patterns (PAMPs), including lipopolysaccharide (LPS) (Hassa et al 2005;Liu et al 2012a;Yang et al 2014;Minotti et al 2015;Bohio et al 2019). Some responses involve the interplay between PARP1 and nuclear factor κB (NF-κB), a key B A Figure 1.…”
Section: Parp1 Induces Macrophage Activation and Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence suggests that ADP-ribosylation participates in inflammation (Bai and Virág 2012;Rosado et al 2013;Kunze and Hottiger 2019). PARP1 has been implicated in the mechanisms for responses (e.g., proinflammatory cytokine expression) of macrophages or macrophage-like cell lines to pathogen-associated molecular patterns (PAMPs), including lipopolysaccharide (LPS) (Hassa et al 2005;Liu et al 2012a;Yang et al 2014;Minotti et al 2015;Bohio et al 2019). Some responses involve the interplay between PARP1 and nuclear factor κB (NF-κB), a key B A Figure 1.…”
Section: Parp1 Induces Macrophage Activation and Inflammationmentioning
confidence: 99%
“…(P) Phosphate group; (ADPr) ADP-ribose; (Ac) acetyl modification; (yellow ciricle) ubiquitin. transcription factor in immunity and various other biological processes (Hassa and Hottiger 1999;Hassa et al 2005;Liu et al 2012a;Minotti et al 2015;Bohio et al 2019;Kunze and Hottiger 2019). Using PARP1-deficient mice Oliver et al (1999) provided evidence that PARP1 promotes NF-κB activation in macrophages in vivo.…”
Section: Parp1 Induces Macrophage Activation and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our study showed that in response to lipopolysaccharide (LPS) or TNF-α exposure, the non-receptor tyrosine kinase c-Abl phosphorylates PARP1 at the conserved Y829 site. Tyrosine phosphorylation of PARP1 is required for PARP1 catalytic activity and NF-κB-dependent pro-inflammatory gene regulation [22]. Actually, a large body of data has now shown that PARP1 functions as a cellular rheostat, promoting different cellular response upon a wide range of type, duration, and strength of stress signals [4].…”
Section: Introductionmentioning
confidence: 99%
“…As the strength of stress stimulus increases, the levels of PARP1 activity and PAR synthesis increase, leading to different cellular outcomes. Weakly activity of PARP1 caused by LPS or TNFα can help cells response inflammation [22,23,24]; Mild or moderate stresses leads to transcription and DNA repair responses that help to maintain genome stability, in contrast, excessive activity of PARP1 resulted the depletion of NAD + and accumulation of PAR, leading some metabolic disorder or cell death [4]. Activated PARP1 accounts for 85%-90% of the total PARP activity in cells, and PARP1 is the most extensively and intensively studied member of the PARP family [3,14,25].…”
Section: Introductionmentioning
confidence: 99%